A diverse diet as an alternative to ryegrass can improve the total antioxidant status of dams at lambing - Garrett, K.; Marshall, C. J.; Beck, M. R.; Maxwell, T. M. R.; Logan, C. M.; Gregorini, P. (Frontiers in Sustainable Food Systems, 2022)
The objective of this experiment was to determine if providing ewes in the final trimester of pregnancy with choice from diverse diet components would reduce markers of oxidative and metabolic stress in ewes and improve lamb birth weights relative to ewes offered only one forage species, repetitively. Fifty-four, twin bearing Coopworth ewes [initial live weight (LW) = 69.82 ± 1.16 kg] were blocked by weight onto iso-energetic diets with either choice from taxonomically diverse plants [DIV; spatially separated strips of ryegrass (Lolium perenne L.), chicory (Cichorium intybus L.), plantain (Plantago lanceolata L.), red clover (Trifolium pratense L.), and alfalfa (Medicago sativa L.)] or a ryegrass only diet (RYE) for the final third of gestation. The ewes offered the DIV diet birthed 8.9% heavier lambs (5.64 ± 0.20 kg) than RYE ewes (5.18 ± 0.20 kg; P = 0.03). In addition, the DIV ewes had greater (P < 0.01) glutathione peroxidase and total antioxidant status, and lower (P = 0.01) plasma non-esterified fatty acid concentrations than the RYE fed ewes 24h after lambing. The results indicate that the DIV diet can improve antioxidant status and reduce some markers of oxidative and metabolic stress at lambing compared to a conventional RYE diet.